Phylogeny and assemblage composition of Frankia in Alnus tenuifolia nodules across a primary successional sere in interior Alaska. Issue 14 (4th June 2013) - Anderson, M. D.; Taylor, D. L.; Ruess, R. W.
Abstract In nitrogen (N) fixing symbioses, host‐symbiont specificity, genetic variation in bacterial symbionts and environmental variation represent fundamental constraints on the ecology, evolution and practical uses of these interactions, but detailed information is lacking for many naturally occurring N‐fixers. This study examined phylogenetic host specificity of Frankia in field‐collected nodules of two Alnus species (A. tenuifolia and A. viridis) in interior Alaska and, for A. tenuifolia, distribution, diversity, spatial autocorrelation and correlation with specific soil factors of Frankia genotypes in nodules collected from replicated habitats representing endpoints of a primary sere. Frankia genotypes most commonly associated with each host belonged to different clades within the Alnus‐infective Frankia clade, and for A. tenuifolia, were divergent from previously described Frankia. A. tenuifolia nodules from early and late succession habitats harboured distinct Frankia assemblages. In early succession, a single genotype inhabited 71% of nodules with no discernable autocorrelation at any scale, while late succession Frankia were more diverse, differed widely among plants within a site and were significantly autocorrelated within and among plants. Early succession Frankia genotype occurrence was strongly correlated with carbon/nitrogen ratio in the mineral soil fraction, while in late succession, the most common genotypes were correlated with different soil variables. Our results suggest that phylogenetic specificity is a significant factor in the A. tenuifolia‐Frankia interaction and that significant habitat‐based differentiation may exist among A. tenuifolia‐infective genotypes. This is consistent with our hypothesis that A. tenuifolia selects specific Frankia genotypes from early succession soils and that this choice is attenuated in late succession.